Isolation of a human epidermal cDNA corresponding to the 180-kD autoantigen recognized by bullous pemphigoid and herpes gestationis sera. Immunolocalization of this protein to the hemidesmosome. - Diaz, L A (1990)
Autoantibodies present in the sera of patients with bullous pemphigoid (BP) bind to the basement membrane zone of normal human skin and commonly recognize two epidermal proteins, the BP240 and BP180 antigens. Two BP antigen cDNA clones from a lambda gt11 human keratinocyte library have been identified on the basis of reactivity with a BP serum. The fusion protein (FP) produced by one clone immunoadsorbed autoantibodies, which specifically recognized the BP180 by antigen, showing no cross-reactivity with BP240 by immunoblot analysis. The FP produced by the second clone immunoadsorbed autoantibodies which specifically reacted with the BP240 epidermal antigen. Northern blot analysis demonstrated that the BP180 and BP240 antigens are encoded by distinct RNA transcripts with lengths of 6.0 and 8.5 kb, respectively. Immunoblot analysis of the BP180 lysogen extract identified a 135-kD FP which was recognized by 7 of 16 BP sera and 7 of 8 herpes gestationis sera. A rabbit antiserum prepared against the lysogenic BP180 FP specifically recognized the BP180 antigen from human epidermal extracts by immunoblotting, labeled the BMZ by indirect immunofluorescence, and bound to human epidermal hemidesmosomes by immuno-electron microscopy. These results indicate that the BP180 antigen recognized by BP and herpes gestationis autoantibodies is a unique hemidesmosomal polypeptide, distinguishable from the BP240 antigen.